Implementasi Kurikulum Merdeka Tingkat Usia 4-5 Tahun - Solikah, Umi; Naning Yuliani (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2025)
Driving schools are schools that are catalysts for realizing the vision of Indonesian education. Children aged 4-5 years are still easy to change in terms of their interests, talents and development so they need more assistance. Free education places student activity as a very important element in this research using qualitative research with the aim of research is to find out the implementation of the free curriculum. and also, what factors are the driving force and obstacles in implementing the independent curriculum at the 4–5-year age level in the TKIT Handayani Menganti driving school. The sources of data in this research are the school principal, class teacher, and TKIT Handayani group A students. This research shows that the implementation of this independent curriculum can make it easier for teachers and children to carry out teaching and learning activities because they can practice directly with their environment, and there is no element of coercion in their interest in learning, because in this independent curriculum children can adapt learning to their interests and talents. Each of them has an inhibiting factor, namely the lack of understanding of parents regarding the implementation of the independent curriculum.